Biomarker of endothelial function for medical prognosis of cardiovascular risk - Loo, Kah Eng (2016)
Endothelial function has been found to result from or lead to numerous cardiovascular diseases such as hypertension, atherosclerosis, diabetes, and coronary artery disease, among others. With almost 30% of Singapore’s population suffering from cardiovascular diseases, the number of people experiencing endothelial dysfunction is extremely significant.